Randal Schweller and Challenges to Realism - حمیرا مشیرزاده; بهرام عین الهی معصوم (رهیافتهای سیاسی و بین المللی)
Randall Schweller is a leading neoclassical realist who has paved the way for the revivalof realism through criticizing the structuralist approach of neo-realism. Waltz, Walt, andMearsheimer have been the major targets of his attacks. This article argues that his mainadded value to realism is to find a way to respond to internal divisions among realists andweak historical support for many of neo-realist propositions. Within this framework he entersinto internal debates among realists about status quo versus revisionist states; explainsnon-formation of balancing behavior and balance of power in the course of history; paysattention to change in international system ignored by many realists; and rejects the objectionsagainst realists for not accounting for international institutions. By including domesticfactors in his analysis, his work accounts for the emergence of revisionist states, dynamicsof international system, and the significance (or insignificance) of international institutionswithin a theory of states’ interest and the resulting balance of interests in the internationalsystem. This theory can clarify the historical conditions in which realists’ claims can proveto be true. In order to give an account of Schweller’s theoretical endeavors to modify and reviverealism, this article analyses his major works and shows that although he could accountfor inconsistences within realism, his own work with its own problems can add to internaldivisions within realist camp.